Phosphoinositide 3-Kinase Delta Regulates Dectin-2 Signaling and the Generation of Th2 and Th17 Immunity - Lee, Min Jung (J Immunol, 2016)
The C-type lectin receptor (CLR) Dectin-2 can trigger the leukotriene C(4) synthase (LTC(4)S)-dependent generation of cysteinyl leukotrienes (cys-LTs) and the CARD9- and NF-κB-dependent generation of cytokines, such as IL-23, IL-6, and TNF-α, to promote Th2 and Th17 immunity, respectively. Dectin-2 activation also elicits the type 2 cytokine IL-33, but the mechanism by which Dectin-2 induces these diverse innate mediators is poorly understood. Here we identify a common upstream requirement for phosphoinositide 3-kinase delta (PI3Kδ) activity for the generation of each Dectin-2-dependent mediator elicited by the house dust mite species, Dermatophagoides farinae (Df), using both pharmacologic inhibition and siRNA knockdown of PI3Kδ in bone marrow-derived dendritic cells (BMDCs). PI3Kδ activity depends on Spleen tyrosine kinase (Syk) and regulates the activity of protein kinase Cδ, indicating that PI3Kδ is a proximal Syk-dependent signaling intermediate. Inhibition of PI3Kδ also reduces cys-LTs and cytokines elicited by Dectin-2 cross-linking, confirming the importance of this molecule in Dectin-2 signaling. Using an adoptive transfer model, we demonstrate that inhibition of PI3Kδ profoundly reduces the capacity of BMDCs to sensitize recipient mice for Th2 and Th17 pulmonary inflammation in response to Df. Furthermore, administration of a PI3Kδ inhibitor during the sensitization of WT mice prevents the generation of Df-induced pulmonary inflammation. These results demonstrate that PI3Kδ regulates Dectin-2 signaling and its DC function.